Periarticular injection and topical tranexamic acid for blood loss control in total knee arthroplasty - Reyes, Francisco; Reyes, Álvaro; Casas-Galindo, Jorge de Francisco (Revista Colombiana de Ortopedia y Traumatología, 2020)
Background: The blood loss during the total knee replacement is one of the main variables that influence the outcomes of this surgery, and several methods have been implemented to reduce it. The aim of the study is to quantify the change in haematocrit and haemoglobin at 24 hours post-surgery in patients subjected to a total primary knee replacement at the Clinica Colombia between March 2016 and August 2017. Methods: An observational study was conducted on a retrospective cohort. The inclusion criteria were those patients who had a total primary knee replacement with periarticular infiltration with bupivacaine, with adrenaline, ketorolac, and morphine, and intra-articular with tranexamic acid. Haemoglobin and pre- and post-operative haematocrit, blood loss calculation, and transfusions were measured. Results: The analysis included a total of 159 total knee replacements (75 conventional prostheses, 84 navigated prostheses). The percentage of transfusion was 0.69% (1 patient). The decrease in mean haematocrit was 7.36%, and the mean decrease in haemoglobin was 2.49 g / dl for a calculated blood loss of 780 ml. A tourniquet was used in 147 patients. Discussion: The combination of tourniquet use, periarticular, and intra-articular injection of tranexamic acid reduces blood loss and the need for tranfusions. Evidence Level: III